2018
DOI: 10.30827/profesorado.v22i2.7732
|View full text |Cite
|
Sign up to set email alerts
|

Modelos Didácticos en la Educación Superior: Una realidad que se puede cambiar

Abstract: Resumen: Los modelos didácticos son planes estructurados que pueden usarse para configurar un currículo, diseñar materiales y orientar la enseñanza en las aulas. El objetivo de la investigación fue determinar la incidencia de los modelos didácticos que aplican los docentes en el rendimiento académico de los estudiantes universitarios. Se utilizó un enfoque cuantitativo, con un diseño no experimental-transversal, de tipo descriptivo y correlacional; se trabajó con una muestra de 179 estudiantes y 4 profesores,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Firstly, theoretical teaching plays a major role in traditional educational methodology. This is based on the transmission of knowledge through an Expositive Approach [8,9] within the established teaching schedule; what is commonly known as master classes [10][11][12]. A practical alternative for adapting the theoretical teaching of the Traditional Model to distance learning is the delivery of master classes through synchronous communication tools, live broadcasted image and sound through virtual platforms such as Big Blue Button, Google Meet, Microsoft Teams, Skype or Zoom.…”
Section: The Traditional Model and Methodological Orientationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, theoretical teaching plays a major role in traditional educational methodology. This is based on the transmission of knowledge through an Expositive Approach [8,9] within the established teaching schedule; what is commonly known as master classes [10][11][12]. A practical alternative for adapting the theoretical teaching of the Traditional Model to distance learning is the delivery of master classes through synchronous communication tools, live broadcasted image and sound through virtual platforms such as Big Blue Button, Google Meet, Microsoft Teams, Skype or Zoom.…”
Section: The Traditional Model and Methodological Orientationsmentioning
confidence: 99%
“…Secondly, practical activity, as opposed to theoretical teaching, plays a minor role in traditional educational methodology. Characterized by repetition, internalization and automation activities outside the established teaching schedule, it is commonly known as homework [10][11][12]. Nevertheless, the distance learning guide recommend some activities of "special relevance" reasonably different from the characteristic homework of the Traditional Model [3].…”
Section: The Traditional Model and Methodological Orientationsmentioning
confidence: 99%
“…y otras por el carácter presupuestario al no poder computar determinadas actividades del profesor dentro de su dedicación docente (De-Miguel et al, 2006). En el ámbito universitario aún predomina el modelo de enseñanza tradicional (Homero, Sosa, y Martínez, 2018) que, si bien puede resultar sumamente efectivo (por ejemplo, para la transmisión de la información de manera rápida a muchos alumnos a la vez (Bará, Domingo, y Valero, 2006)), no siempre garantiza aprendizajes significativos (Martín et al, 2021) ni favorece la interdisciplinariedad, ni facilita la aplicación del conocimiento a casos reales, entre otras muchas limitaciones (Bará et al, 2006). En un estudio llevado a cabo por Cañabate et al (2014) en los grados de Magisterio y Psicología, se concluye que la clase magistral continúa siendo la metodología docente más utilizada en la universidad, aunque existe un incremento en el uso de metodologías más activas como el análisis de casos, el Aprendizaje Basado en Problemas, el Aprendizaje Basado en Proyectos, el cooperativo y el aprendizaje reflexivo.…”
Section: Metodologías Docentes En El Sistema Universitariounclassified
“…The creation and implementation of didactic experiences has focused on interactions that benefit the teaching-learning process and the sustainable development of university students. This has been achieved through the acquisition of competencies and skills that are in accordance with the expected learning and with the criteria established for the achievement of such expected learning [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, some models that teachers use at university, including traditional, technological, spontaneous or active, and constructivist or alternative-investigative, have been characterized [3]. For example, in a study of students of educational and technological sciences at an Ecuadorian university, it was reported that the technological and spontaneous-active models used by teachers were the best predictors of academic achievement [4].…”
Section: Introductionmentioning
confidence: 99%